STUDI PENYEBARAN GURU SMPN SE-KABUPATEN HULU SUNGAI SELATAN - Chairil Faif Pasani; Ahmad Naparin; Sri Hartini (FKIP ULM, 2015)
One parameter of the professionalism of teachers is teachers teach according to their fields. Therefore, dissemination of subject teachers of each school should be evenly distributed. This study is aimed to describe the spread of the teachers at the Junior High School (SMP) as Hulu Sungai Selatan (HSS). This type of research is a survey. The subjects were teachers throughout the district SMP HSS. Data were collected through: questionnaires, interviews, observation and documentation. The results showed the overall number of teachers for the subjects of Religious Education and Character , Pancasila and Citizenship Education ( PPKn ) , Indonesian , English, Mathematics , Natural Sciences (IPA), Social Sciences ( IPS ) , and Physical Education and Health has been fulfilled , but the distribution is yet uneven.